PENGARUH STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X SMK NEGERI 1 MOJOANYAR: PENGARUH STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X SMK NEGERI 1 MOJOANYAR - Yustina Wulandari; Achmad Noor Fatirul; Sunyoto Hadi Prayitno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of Problem Based Learning (PBL) learning strategies and learning interest on the learning outcomes of class X students at SMK Negeri 1 Mojoanyar. The method used is an experiment with a post-test control group design. The instruments used are learning outcome tests and learning interest questionnaires. Data were analyzed using ANOVA tests to test for significant differences between groups taught with PBL and Expository Strategy and the effect of learning interest on learning outcomes. The results of the analysis show that PBL is more effective in improving student learning outcomes compared to Expository Strategy, with an F value = 87.568 and a significance of 0.000. In addition, learning interest also has a significant effect on student learning outcomes, with an F value = 9.151 and a significance of 0.003, indicating that students with high learning interest have better learning outcomes. The results of the interaction test show a significant effect between learning strategies and learning interest on learning outcomes, with an F value = 5.463 and a significance of 0.021. The conclusion of this study is that PBL is more effective in improving learning outcomes than Expository Strategies, and learning interest plays a significant role in achieving learning outcomes. The implications of this study are the need to implement PBL in learning and pay attention to student learning interests to design more effective learning. Teachers are expected to adapt learning strategies to student interests to achieve optimal results.